ANALISIS PERSEPSI, SIKAP DAN MOTIVASI KONSUMEN TERHADAP MINAT PENGGUNAAN PRODUK KARTU KREDIT AFFINITY XXXX-USU PADA DAERAH PEMASARAN WILAYAH MEDAN - Indra Maratama (Al-Irsyad: Jurnal Pendidikan dan Konseling, 2016)
Affinity Card can be used as an identification card associations, alumni associations and others. At this year PT. XXXX bank is targeting a credit card co- branding and affinity contribute 15% to the target of credit card transactions from 2:08 Million credit card of the total target credit card PT. Bank XXXX 2013. Acquisition of affinity credit card marketing on the month September 2014 the marketing area Terrain area amounts to 886 cards from all three universities that cooperate with the details of Affinity USU 236 cards, 305 cards from Affinity UNIMED and 345 of Affinity UNSYAH. XXXX Bank has undertaken various strategies in marketing their credit card but has yet to get maximum results, it is not certain what the cause. For the sake of getting the most-needed improvements in credit card marketing strategy is to understand what the perceptions, attitudes and motivation of potential customers. The results of writing that has been done, after going through the stage of data collection, data processing, data analysis and the final interpretation of the results of the analysis of the influence of Perception, Attitudes and Motivation Consumers AgainstInterests Product Use Credit Cards Affinity Bank XXXX-USU On Regional Marketing Regional Medan, the conclusions to be drawn together (simultaneously) variable Perceptions, Attitudes and Motivation significant effect on the dependent variable interest. The significant value of the three independent variables is <0.05, indicating that the variableperception, attitude, motivation has a significant influence ter-facing Minat.Arah regression coefficient is positive, it means that any increase in Perceptions, Attitudes and Motivation clients will Interest-kan increased use of affinity credit cards Bank XXXX-USU.Keywords: Konsumen Bank, Minat, Sikap, Motivasi.